Analysis of Factor Affecting Customer Purchase Shopping Live Shop - Liang Miladi Budhaye; Tanty Oktavia (Universitas Sulawesi Barat, 2023)
The rise of online shopping, particularly through e-commerce platforms, has given rise to a new phenomenon called live shopping. Live shopping involves sellers creating virtual shopping experiences that are directly accessible to potential buyers. This study aims to identify the factors that influence buyers when making purchases in live shopping marketplaces, utilizing a basic model derived from the Technology Acceptance Model. The research employs a quantitative research method and utilizes the SmartPLS software. The findings of this study demonstrate that all indicators significantly impact Customer Purchase Shopping Live Shop. These factors include Information Quality, Intention to Use, Perceived Ease of Use, and Perceived Usefulness. The main implication of this research is that stakeholders in the live shopping industry should focus on providing comprehensive product information, ensuring seamless transactions, creating an engaging atmosphere with product tips, offering promotions to attract customers, and prioritizing product quality. This is due to the significant role of complete and honest information in making purchases on social media platforms.